Competencies of Basic Education Teachers and Performance of Learners in 2017-2018 National Achievement Test in the Philippines - Francisco, Ronald; Caingcoy, Manuel (Jurnal Pendidikan Progresif, 2022)
Objectives: The study determined the competencies of teachers and performance of learners in 2017-2018 National Achievement Test. It identified the influence of teachers’ competencies on performance of learners. Methods: It employed descriptive-correlational and explanatory designs and it involved three divisions in Northern Mindanao region, Philippines.   Findings: The Grade 10 and 6 teachers have possessed very satisfactory competencies across areas, while the Grade 10 and Grade 6 learners had a low mastery and very low mastery, respectively. Furthermore, there was no significant relationship between the competencies of teachers and the performance of learners, while their competencies did not significantly influence the performance of learners. Conclusion: Teachers were deemed competent in all areas and learners had not acquired most of the competency standards of the curricula. Hence, no matter how competent teachers are, this would not contribute significantly to improving the performance of learners in the National Achievement Test. Thus, competencies of teachers cannot determine the performance of learners. Keywords: competencies of teachers, performance of learners, national achievement test.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202212